One Health Index applied to countries in South America - Sibim, Alessandra Cristiane; Chiba de Castro, Wagner Antonio; Kmetiuk, Louise Bach; Biondo, Alexander Welker (Frontiers in Public Health, 2024)
The One Health concept has proposed an integrated and unified approach, aiming health balance and enhancement by recognizing the interdependence of human, animal, and environmental health.The COVID-19 pandemic has pushed global One Health initiatives and policy improvement toward preventive measures for future pandemics, particularly of zoonotic origin. Such scenario may be particularly relevant for South America, considered highly vulnerable due to natural biodiversity superposed to socioeconomical and environmental issues, demanding effective methods and indicators for proper One Health strategies and goals, aligned to macroregional contexts. Accordingly, the present study has aimed to assess the One Health Index (OHI) in South American countries, along with potential interactions with socioeconomical indicators. Results obtained by Clustering Analysis and Permutational Multivariate Analysis of Variance (PERMANOVA) have revealed a positive association between OHI and Human Development Index (HDI), but not with Gross Domestic Product (GDP).Although South American countries with political stability, robust investment in health and progressist policies have shown a higher OHI, better environmental health was not associated to better human and animal health. In addition, although the Amazon biome (which overlaps 9/12 South American countries) had a positive impact to environmental health, such contribution contrasted to rudimentary local human health systems and may highlight the complexity of One Health within the South American context. Lack of stronger indicators for animal health was also considered an important weaking point for a true OHI assessment. Nonetheless, countries with more developed livestock have presented better animal health, which may not reflect an overall animal health indicator, as companion and wildlife animal health indicators were not available. Although lower (within-country) scale analysis such as states and metropolitan areas may better shape internal differences, the study herein has clearly shown One Health inequalities and challenges among South American countries. As important, forests and other natural areas of developing (particularly Amazon Forest) countries should receive incentives for sustainable economic growth, preventing the sacrifice of environmental health in benefit of human and livestock animal health.